Heterogeneity of neuroblastoma cell lines in insulin‐like growth factor 1 receptor/Akt pathway‐mediated cell proliferative responses. Issue 9 (25th June 2013) - Qi, Lei; Toyoda, Hidemi; Shankar, Vipin; Sakurai, Naoto; Amano, Keishirou; Kihira, Kentaro; Iwasa, Tadashi; Deguchi, Takao; Hori, Hiroki; Azuma, Eiichi; Gabazza, Esteban C.; Komada, Yoshihiro
<x xml:space="preserve">Abstract</x> Insulin‐like growth factor 1 receptor (IGF‐1R) is critical for cancer cell proliferation; however, recent clinical anti‐IGF‐1R trials did not show clear clinical benefit in cancer therapy. We hypothesized that IGF‐1R signaling‐mediated proliferative response is heterogeneous in neuroblastoma (NB) cells, and analyzed the cell growth of 31 NB cell lines cultured in three different media, including Hybridoma‐SFM medium (with insulin) and RPMI1640 with/without 10% FBS. Three growth patterns were found. In response to IGF and insulin, cell proliferation and Akt phosphorylation were upregulated in 13 cell lines, and suppressed by MK2206 (Akt inhibitor) and picropodophyllin (IGF‐1R inhibitor). Interestingly, 3 of these 13 cell lines showed Akt self‐phosphorylation and cell proliferation in RPMI1640; their proliferation was downregulated by anti‐IGF‐1 or anti‐IGF‐2 neutralizing antibody, suggesting the existence of an autocrine loop in the IGF‐1R/Akt pathway. Eighteen NB cell lines did not proliferate in RPMI1640, even though Akt phosphorylation was upregulated by IGF and insulin. Based on the heterogeneous response of the IGF‐1R/Akt pathway, the 31 NB cell lines could be classified into group 1 (autocrine IGF‐mediated), group 2 (exogenous IGF‐mediated) and group 3 (partially exogenous IGF‐mediated) NB cell lines. In addition, group 3 NB cell lines were different from group 1 and 2, in terms of serum starvation‐induced caspase 3 cleavage and picropodophyllin‐induced G2/M arrest. These results indicate that the response of the IGF‐1R/Akt pathway is an important determinant of the sensitivity to IGF‐1R antagonists in NB. To our knowledge, this is the first report describing heterogeneity in the IGF‐1R/Akt‐mediated proliferation of NB cells.